Plant communities in tropical ancient mountains: How are they spatially and evolutionary structured? - De Mattos, Jacqueline S.; Morellato, Leonor Patrícia Cerdeira [UNESP]; Batalha, Marco Antonio (Oxford University Press (OUP), 2021)
The integration of phylogenetic methods and species distribution can really help in the investigation of biogeographic patterns and to fill gaps in evolutionary ecology. Here we investigated how the vascular flora of the Brazilian ancient Cipó Mountains, an alleged OCBIL (old, climatic buffered infertile landscape) with a high diversity of species and endemism, evolved across that harsh archipelago-like system and altitudinal gradient. We used a node-based analysis of species distributions that follows the concepts of over- and underrepresentation and takes into account the relationship between sister clades, to yield two very statistically tractable metrics: the geographical node divergence and specific over-representation score. We collected and identified plant species along an elevational gradient ranging from 800 to 1400 m a.s.l. We also collected environmental variables such as elevation and soil properties. We found three allopatric nodes, which revealed the major biogeographic shifts in this tropical mountaintop vegetation. We found evidence to support the idea that environmental filtering is significantly shaping the distribution of biological communities and is restraining clades in the phylogeny. We argue that our study offers new insights into the biogeographic history and distributional shifts of the ancient rocky grasslands flora and to mountaintop vegetation systems in general.
Keywords: elevational gradient; OCBIL; phylogenetic structure; phylogeny; plant distribution; rocky grasslands